Pengaruh Model Pembelajaran Project Based Learning (PjBL) Berbantukan Media Gambar terhadap Kemampuan Menulis Puisi pada Siswa Kelas X MA Al Imarah Bajulmati - Uswatun Hasanah; Ulya Nurul Laili; Mardiana Ulfa; Ririn Nurul Azizah; Risalatun Nikmah (Jurnal Multidisiplin Indonesia, 2026)
This study aims to determine the effect of the Project Based Learning model on poetry creativity in class X students of Madrasah Aliyah (MA) Al Imarah. The population of this study was all class X students of Madrasah Aliyah (MA) Al Imarah totaling 58 students. The sampling technique was the Purposive Sampling technique. The sample in this study was all class X-B students totaling 30 students. This study was classified into pre-experimental design research with the design used being the one group. The tests used were pretest (initial test) and posttest (final test). Based on the results of the study, it was concluded that the ability to write poetry by students of X-B Madrasah Aliyah (MA) Al Imarah before using the Project Based Learning model was in the good category with an average of 71.66. The ability to write poetry by students of X-B Madrasah Aliyah (MA) Al Imarah after using the Project Based Learning model was in the very good category with an average of 84.44. Based on the statistical analysis, the average pretest and posttest scores were -12.777, with a 2-tailed significance level of 0.000. Therefore, Ha was accepted and H0 was rejected. This indicates that the use of the Project-Based Learning model significantly impacted the poetry writing skills of class X-B students at Al Imarah Islamic Senior High School (MA).